Antisemitism before the Holocaust : re-evaluating antisemitic exceptionalism in Germany and the United States, 1880-1945 - Frankel, Richard E. 2005- (Routledge studies in modern history, 2023)
"This book examines the history of antisemitism in the United States and Germany in a novel way by placing the two countries side by side for a sustained comparison of the anti-Jewish environments in both countries from the 1880s to the end of the Second World War. Author Richard Frankel shatters the widely-held notion of exceptionalism in Germany and America: the belief that antisemitism in Germany was uniquely murderous and led inevitably to the Holocaust and that antisemitism in the United States was uniquely benign, making an American Holocaust all but unthinkable. In a series of new and previously published essays that have been revised, updated, and expanded, the book relates antisemitism to issues including Jewish and Chinese immigration, discrimination and exclusion, the First World War and its aftermath, Hitler and Henry Ford, Nazis, the American Right, and the Roosevelt Administration, and a German Ku Klux Klan. Taken together, these essays reveal that antisemitism in Germany was less aberrant than commonly believed and that American antisemitism was indeed dangerous and more similar to what existed in Germany during the same period. Antisemitism Before the Holocaust is an essential volume for students and scholars alike interested in European and American history, the history of the holocaust and the First World War"--